Preparation method of imidazole-containing meta-position aramid fiber membrane and battery
By introducing flexible segment mPEG and imidazole ring structures into lithium-ion battery separators, the thermal stability and film-forming properties of lithium-ion battery separators are solved, thereby achieving high efficiency, improved cycle life, and enhanced safety of lithium metal batteries.
Patent Information
- Application Number
- CN202511202144.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-12-05
AI Technical Summary
Existing lithium-ion battery separators have poor thermal stability and cannot effectively control lithium deposition behavior, resulting in short cycle life and safety hazards. Traditional polyolefin separators cannot completely replace meta-aramids, and imidazole-containing meta-aramid films are brittle and cannot be formed.
Flexible segment mPEG is introduced during the polymerization stage, and an imidazole-containing meta-aramid membrane is prepared by a non-solvent phase separation method. Combined with the chemical coordination of benzimidazole ring and amino group, a nanoscale microphase separation structure is formed, which improves toughness and film-forming properties, and is applied to the separator and negative electrode protection of lithium metal batteries.
It significantly improves the cycle life and safety of lithium metal batteries. The introduction of flexible segments reduces stress concentration, enhances the toughness and interfacial stability of the film, inhibits dendrite growth, and improves electrolyte wettability and thermal stability.
Smart Images

Figure CN121064474A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the preparation and technical application field of heterocyclic meta-aramid film, in particular to a preparation method of imidazole-containing meta-aramid film and a battery. BACKGROUND
[0002] With the explosive growth of demand for new energy vehicles and portable energy storage devices, high-energy-density lithium metal batteries are considered as the core of the next generation of energy storage technology. However, the uncontrollable dendrite growth, volume expansion and side reactions of lithium anode during the cycling process not only lead to rapid capacity decay, but also bring safety hazards. The most widely used separator in lithium-ion batteries is polyolefin porous film, such as polyethylene (PE), polypropylene (PP), or their blends, which is due to their thin thickness and small pore size. However, the heat resistance of this polyolefin is not good enough, which limits its application in power batteries from the safety aspect. Their poor thermal stability will cause thermal shrinkage when abnormally heated. In addition, the poor compatibility of polyolefin membranes with liquid electrolytes will shorten the cycle life of the battery. Although polyolefin membranes have thermal shutdown characteristics, the huge heat generated during the operation of lithium-ion batteries will cause the internal temperature of the battery to rise, inducing uneven heat distribution, and even causing thermal runaway. Traditional polyolefin separators have high chemical inertness, poor thermal stability, and are difficult to balance mechanical strength and electrolyte wettability, and cannot effectively regulate lithium deposition behavior. Meta-aramid (PMIA) has excellent heat resistance, flame resistance and film-forming property due to its aromatic ring skeleton and amide network, but its molecular chain polarity is insufficient and its lithium affinity is limited, which limits the interface stability. The cost of aramid is also relatively high compared to traditional polyolefin, so it is also impossible to completely replace polyolefin separators. Introducing heterocyclic structures containing nitrogen elements into it is expected to improve the cycle life of the battery. However, the current research on imidazole-containing meta-aramid is still in the synthesis stage, only focusing on the change of system viscosity, and lacks systematic exploration for practical application. The single-component aramid prepared from PABZ, MPD and IPC has high brittleness after blade coating and cannot form a film, which limits its functional application. Therefore, in view of the above defects, the present application introduces a flexible chain segment mPEG in the polymerization stage, which significantly improves the toughness and film-forming integrity of the film; and then successfully applies the modified aramid film to lithium metal anode protection and separator integration scenarios, realizing effective connection from synthesis to application. SUMMARY
[0003] In view of the problem that the imidazole-containing meta-aramid resin film obtained by the non-solvent phase separation method is brittle and cannot be shaped, the present application provides a preparation method of imidazole-containing meta-aramid film and a battery.
[0004] A preparation method of imidazole-containing meta-aramid film, comprising the following steps: Step 1: under nitrogen atmosphere, stirring LiCl powder and DMAc solution to obtain solution A; Step 2: dispersing mPEG powder in solution A, stirring to obtain solution B; Step 3: adding MPD powder and PABZ powder to solution B to obtain solution C; Step 4: cooling solution C to-20~0℃, adding IPC to the cooled solution C to obtain colloid D; Step 5: heating and stirring colloid D, centrifugal defoaming and scraping to obtain film F1; Step 6: placing film F1 in a coagulation bath to obtain film F2; Step 7: sequentially performing vacuum heat pressing pre-drying and vacuum drying on film F2 to obtain imidazole-containing meta-aramid film G2.
[0005] Preferably, in step 1, the nitrogen gas needs to be introduced in advance before synthesis, and needs to be continuously introduced for 15~30 min. And it also needs to be continuously introduced during the synthesis until the synthesis is completed; the stirring speed is always kept at 1000~1500 r / min; The mass ratio of DMAc solution to LiCl powder is 100:2~5, the stirring time is 20~60 min, and the stirring temperature is 20~30℃.
[0006] Preferably, in step 2, the addition amount of mPEG powder is 5%~10% of the mass of solution A, the stirring time is 20~60 min, and the stirring temperature is 20~30℃.
[0007] Preferably, in step 3, the molar ratio of MPD powder to PABZ powder is 3:(1~6), the stirring and dissolving time is 20~60 min, and the stirring temperature is 20~30℃.
[0008] Preferably, in step 4, the molar ratio of the sum of MPD powder and PABZ powder to IPC powder is 1:(1~1.02), the low-temperature polycondensation time is 20~60 min, and the low-temperature polycondensation temperature is 0~-20℃.
[0009] Preferably, in step 5, when heating and stirring, first heat colloid D to 25~65℃, and then continuously stir for 20~60 min under the condition of maintaining the temperature; When centrifugal defoaming, the speed is 6000-8000 r / min, and the time is 3~10 min; When scraping, the temperature is 20~30℃, the speed is 5~20 mm / s, and the thickness is 50~75 μm.
[0010] Preferably, in step 8, the coagulation bath is any one or several of H2O, C2H5OH, CH3OH, C3H8O3, DMAc / H2O, C2H5OH / DMAc or CH3OH / DMAc, and the displacement time is 12-24 h.
[0011] Preferably, in step 10, the temperature during vacuum pre-drying is 65-105℃, the time is 1-3 min, and the vacuum degree is -0.1--0.09 MPa. During vacuum drying, the temperature is 60-80℃, the time is 12-24 h, and the vacuum degree is -2.5--3 MPa.
[0012] An imidazole-containing meta-aramid film G2 obtained by a preparation method of the imidazole-containing meta-aramid film.
[0013] A battery, which is assembled in the order of positive electrode shell-positive electrode-separator-thin film H-negative electrode-gasket-spring piece-negative electrode shell, wherein the thin film is cut from the imidazole-containing meta-aramid film G2 obtained by the preparation method.
[0014] Compared with the prior art, the present application has the following beneficial effects: The preparation method of the imidazole-containing meta-aramid film of the present application introduces mPEG into the synthesis process of the imidazole-containing meta-aramid, prepares an imidazole-containing meta-aramid film, and applies it to the field of battery separator and lithium metal negative electrode protection, thereby widening the application field of the imidazole-containing meta-aramid.
[0015] Specifically, first, the introduction of mPEG inserts a flexible polyether segment into the main chain of the imidazole-containing meta-aramid, reduces the glass transition temperature and melt viscosity of the system, acts as an "internal plasticizer", and makes the segment maintain sufficient fluidity during the solvent evaporation stage; at the same time, the hydrophilic mPEG and the rigid imidazole ring undergo nanoscale microphase separation to form hard-soft alternating microzones, which not only retain the skeleton strength of the imidazole-containing aramid, but also absorb stress and passivate cracks through the soft zones, significantly improving the elongation at break. In addition, mPEG delays solvent evaporation and reduces surface energy, effectively inhibiting stress concentration and shrinkage, and ultimately transforming the originally brittle and unformed aramid system into a ductile network that can be large-area, defect-free and scraped to form a film, thereby completely solving the film forming problem.
[0016] The main reason for placing the thin film H between the negative electrode and the separator in the battery of the present application is that the application of the imidazole-containing meta-aramid to the field of battery separator and negative electrode protection is due to the tertiary amine (-N=) and the terminal amino group (-NH2) on the benzimidazole ring, which can form a stable passivation film on the surface of lithium metal, effectively preventing the direct contact between lithium metal and electrolyte, and preventing the occurrence of dendritic lithium and lithium deposition. +Lewis acid-base coordination, uniform lithium ion flux, and inhibition of dendrite nucleation. The imidazole ring can also form N-Li bonds with the surface of metallic lithium, generating a stable SEI rich in nitrogen and fluorine (if the system contains fluorine), reducing interfacial side reactions. Second, the rigid aromatic heterocycle of PABZ + hydrogen bond network can increase the modulus of the separator, reduce the thermal shrinkage of the separator, and physically block the penetration of dendrites. Third, the high glass transition temperature (Tg) of the meta-aramid containing imidazole makes the separator remain stable in size at high temperature. Fourth, the polarity of imidazole / amino improves the wettability of the electrolyte, reduces the interfacial impedance, and reduces the capacity decay caused by concentration polarization. Fifth, the introduction of the diamino imidazole heterocycle can also inhibit "dead lithium" to some extent, uniformize deposition / detachment, reduce irreversible lithium loss, and keep the coulombic efficiency high in the long term. In short, PABZ can significantly prolong the cycle life of lithium metal batteries through chemical coordination uniformization + physical strengthening of dendrites + interfacial stabilization, triple action. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 A flowchart of a preparation method of an imidazole-containing meta-aramid film according to the present application; Figure 2 A synthesis reaction equation of an imidazole-containing PMIA with mPEG introduced therein according to the present application; Figure 3 A comparison diagram of coulombic efficiency in a Li / Cu half-cell of a battery assembled by Example 1 of the present application and a battery assembled by a PP separator. DETAILED DESCRIPTION
[0018] The embodiments of the present application will be described in detail by the following specific examples, and other advantages and effects of the present application can be easily understood by those skilled in the art from the contents disclosed in the present specification.
[0019] Exemplary embodiments of the present application will now be described with reference to the accompanying drawings, however, the present application can be implemented in many different forms and is not limited to the embodiments described herein, which are provided to fully and completely disclose the present application and to fully convey the scope of the present application to those skilled in the art. The terms used in the exemplary embodiments represented in the accompanying drawings are not limited to the present application. In the drawings, the same elements / elements are designated with the same reference numerals.
[0020] Unless otherwise defined, the terms (including technical terms) used herein have meanings commonly understood by those skilled in the art. In addition, it can be understood that the terms defined in commonly used dictionaries should be understood to have meanings consistent with the context of the relevant art, and should not be understood as ideally or excessively formal meanings.
[0021] The application will be further described in detail below with specific examples, which are intended to explain but not limit the application.
[0022] The application discloses a preparation method of an imidazole-containing meta-aramid film, which comprises the following steps: Figure 1 Step 1: uniformly stirring LiCl powder and a DMAc solution in a nitrogen atmosphere to obtain solution A. Specifically, nitrogen is introduced into a three-necked flask, and air in the flask is exhausted, then lithium chloride (LiCl) powder and a N,N-dimethylacetamide (DMAc) solution are added into the three-necked flask, and solution A is obtained by uniformly stirring.
[0023] The introduced nitrogen needs to be introduced in advance before synthesis, and needs to be continuously introduced for 15-30 min. The stirring speed is always kept at 1000-1500 r / min during the synthesis process. The mass ratio of the DMAc solution to the LiCl powder is 100:2-5, the stirring time is 20-60 min, and the stirring temperature is 20-30 DEG C.
[0024] Step 2: dispersing mPEG powder (methoxy polyethylene glycol) in solution A, and uniformly stirring to obtain solution B.
[0025] The added amount of the mPEG powder is 5%-10% of the mass of solution A, the stirring time is 20-60 min, and the stirring temperature is 20-30 DEG C.
[0026] Step 3: adding MPD (meta-phenylenediamine) powder and PABZ (2-(4-aminophenyl)-5-aminobenzimidazole) powder into solution B to obtain solution C.
[0027] The molar ratio of the MPD powder to the PABZ powder is 3: (1-6), the stirring and dissolving time is 20-60 min, and the stirring temperature is 20-30 DEG C.
[0028] Step 4: cooling solution C to-20-0 DEG C, and adding IPC (isophthaloyl dichloride) into the cooled solution C to obtain colloid D.
[0029] The molar ratio of the sum of the MPD powder and the PABZ powder to the IPC powder is 1: (1-1.02), the low-temperature polycondensation time is 20-60 min, and the low-temperature polycondensation temperature is 0--20 DEG C.
[0030] Step 5: heating and stirring colloid D, centrifuging and defoaming, and scraping and coating to obtain thin film F1. Step 501: first heat the colloid D to 25-65℃, then continuously stir for 20-60 min under the condition of keeping the temperature, to obtain colloid E1; Step 502: centrifugal defoaming of the colloid E1 to obtain colloid E2; wherein the speed is 6000-8000 r / min, and the time is 3-10 min; Step 503: using a doctor blade to coat the colloid E2 on a glass plate to obtain film F1, wherein the coating temperature is 20-30℃, the coating speed is 5-20 mm / s, and the coating thickness is 50-75 μm.
[0031] Step 6: placing the film F1 in a coagulation bath to replace, to obtain film F2; wherein the coagulation bath is any one or several of H2O, C2H5OH, CH3OH, C3H8O3, DMAc / H2O, C2H5OH / DMAc or CH3OH / DMAc, and the replacement time is 12-24 h.
[0032] Step 7: vacuum heat pressing pre-drying and vacuum drying of the film F2 in sequence to obtain the imidazole-containing meta-aramid film G2, specifically: Step 701: pre-drying of the film F2 in a vacuum heat pressing drying machine; wherein the temperature is 65-105℃, the time is 1-3 min, and the vacuum degree is -0.1--0.09 MPa; Step 702: placing the film G1 into a vacuum drying oven to dry overnight to obtain the imidazole-containing meta-aramid film G2; wherein the temperature is 60-80℃, the time is 12-24 h, and the vacuum degree is -2.5--3 MPa.
[0033] The preparation method of the imidazole-containing meta-aramid film of the present application is to introduce mPEG into the synthesis process of the imidazole-containing meta-aramid, and prepare the imidazole-containing meta-aramid film. Specifically, the whole process before synthesizing the colloid E1 needs to be protected by nitrogen to prevent the side reaction of the reagents with oxygen in the air during the synthesis process, thereby reducing the polymerization degree of the system. First, a LiCl / DMAc complex system is prepared to ensure the sufficient dissociation of the hydrogen bond between the aramid chains in the subsequent process, and the colloid E2 with a suitable blade coating viscosity is formed; second, the solution B is obtained after adding the flexible mPEG toughening agent, and then the two amine monomers MPD and PABZ and IPC are introduced for low-temperature polycondensation, and the low temperature (-20~0°C) is used to inhibit the side reaction and quickly generate the colloid D with high polymerization degree. Then, the temperature is increased for stirring to restore the segment mobility, the bubbles are removed by centrifugal defoaming, the integrity of the subsequent film is ensured, and the wet film F1 with a thickness of 50~75 μm is obtained by blade coating. The phase separation and micro-porous structure are induced by replacing the coagulation bath (water / alcohol / glycerol or mixed solvent) to obtain the film F2; the film is flat and a part of the organic solvent is quickly removed by vacuum heat pressing pre-baking (65~105°C, -0.1~-0.09 MPa), and then the film is vacuum dried overnight (60~80°C, -2.5~-3 MPa) to completely dehydrate and shape the film, and finally the imidazole-containing meta-aramid functional film G2 is obtained, which has toughness and micro-porous network and can be directly used for lithium metal battery negative electrode protection or separator.
[0034] Example 1 Step 1, nitrogen was introduced into a three-necked flask 15 min in advance, and the air in the flask was exhausted, then LiCl powder and N,N-dimethylacetamide DMAc solvent were added to the three-necked flask in a mass ratio (50:1), and mechanical stirring was carried out at 20°C and a speed of 1000 r / min for 20 min to obtain solution A; Step 2: mPEG powder was added to solution A at 10% of the amount of the final synthesized meta-aramid resin, and mechanical stirring was carried out at 20°C and a speed of 1100 r / min for 25 min to obtain solution B; Step 3: MPD powder and PABZ powder were dissolved in solution B in a molar ratio of (3:1) by mechanical stirring at 25°C and a speed of 1100 r / min for 20 min to obtain solution C; Step 4: the temperature of solution C was reduced to -20°C, and then IPC was added in a molar ratio of (1:1) to MPD+PABZ for low-temperature polycondensation for 20 min to obtain colloid D; Step 5: colloid D was heated and stirred, centrifuged and defoamed, and then blade coated to obtain film F1; specifically: Step 501: the temperature of colloid D was increased to 25°C, and mechanical stirring was continuously carried out at a speed of 1100 r / min for 25 min to obtain colloid E1; Step 502; centrifugal defoaming colloid E1 at 6000 r / min for 3 min to obtain colloid E2; Step 503: using a drawdown coater to draw down colloid E2 on a glass plate at a drawdown temperature of 20℃, a drawdown speed of 5 mm / s and a drawdown thickness of 50 μm to obtain film F1; Step 6: placing film F1 in coagulation bath H2O for 12 h to obtain film F2; Step 7: sequentially performing vacuum heat pressing pre-drying and vacuum drying on film F2 to obtain imidazole-containing meta-aramid film G2, specifically: Step 701: pre-drying film F2 in a vacuum heat pressing dryer at 60℃ under a vacuum degree of -0.1 MPa for 1 min to obtain film G1; Step 702: placing film G1 into a vacuum drying oven at a temperature of 60℃ and a vacuum degree of -2.5 MPa for drying overnight for 12 h to obtain imidazole-containing meta-aramid film G2.
[0035] Step 8: punching film G2 into a circular film with a diameter of 19 mm to obtain film H; Step 9: assembling film H in the battery according to the order of positive shell-positive electrode-separator-film H-negative electrode-gasket-spring piece-negative shell to obtain the battery.
[0036] The battery prepared in Example 1 was tested in a Li / / Cu half-cell at a current density of 1.0 mA·cm -1 The average coulombic efficiency of the Li / / Cu half-cell with the film H added in Example 1 reached 83.92%, which was better than that of the traditional polyolefin separator (78.84%).
[0037] Example 2 Step 1, 20 min in advance, nitrogen was introduced into a three-necked flask, and the air in the flask was exhausted, then LiCl powder and N,N-dimethylacetamide (DMAc) solvent were added to the three-necked flask at a mass ratio (100:3), and mechanical stirring was carried out at 25℃ at a speed of 1100 r / min for 25 min to obtain solution A; Step 2: adding mPEG powder at 20% of the amount of the final synthesis of meta-aramid resin to solution A, and mechanically stirring at 25℃ at a speed of 1200 r / min for 30 min to obtain solution B; Step 3: dissolving MPD powder and PABZ powder in solution B at a molar ratio of (1:1) at 25℃ with mechanical stirring at a speed of 1200 r / min for 30 min to obtain solution C; Step 4: After solution C is cooled to -15℃, IPC is added at a molar ratio of (1:1.02) to MPD+PABZ, and low-temperature polycondensation is performed for 25 min to obtain colloid D; Step 5: Colloid D is heated and stirred, defoamed by centrifugation, and scraped to obtain thin film F1; specifically: Step 501: Colloid D is heated to 30℃ and mechanically stirred at a speed of 1100 r / min for 30 min to obtain colloid E1; Step 502: Colloid E1 is defoamed by centrifugation at a speed of 7000 r / min for 5 min to obtain colloid E2; Step 503: Colloid E2 is scraped onto a glass plate using a scraper at a scraping temperature of 30℃, a scraping speed of 10 mm / s, and a scraping thickness of 60 μm to obtain thin film F1; Step 6: Thin film F1 is placed in a coagulation bath H2O for 24 h to obtain thin film F2; Step 7: Thin film F2 is sequentially subjected to vacuum heat pressing pre-drying and vacuum drying to obtain imidazole-containing meta-aramid film G2; specifically: Step 701: Thin film F2 is pre-dried in a vacuum heat pressing dryer at 65℃ under a vacuum degree of -0.1 MPa for 1 min to obtain thin film G1; Step 702: Thin film G1 is placed in a vacuum drying oven at a temperature of 70℃ and a vacuum degree of -2.5 MPa for drying overnight for 24 h to obtain imidazole-containing meta-aramid film G2; Step 8: Thin film G2 is punched into a circular film with a diameter of 19 mm to obtain thin film H; Step 9: Thin film H is assembled in the battery according to the order of positive shell-positive electrode-separator-thin film H-negative electrode-gasket-elastic piece-negative shell to obtain the battery.
[0038] The battery prepared in Example 2 is tested in a Li / / Cu half-cell at a current density of 1.0 mA·cm -1 The average coulombic efficiency of the Li / / Cu half-cell with the thin film H of Example 2 reaches 87.65%, which is better than that of the traditional polyolefin separator (78.84%).
[0039] Example 3 Step 1: Nitrogen is introduced into a three-necked flask 30 min in advance, and the air in the flask is exhausted. Then LiCl powder and N,N-dimethylacetamide (DMAc) solvent are added to the three-necked flask at a mass ratio of (25:1), and mechanically stirred at a speed of 1500 r / min at 30℃ for 30 min to obtain solution A; Step 2: mPEG powder was added to solution A at 30% of the final synthesis meta-aramid resin amount, mechanically stirred at 1500 r / min for 30 min at 30°C to obtain solution B; Step 3: MPD powder and PABZ powder were dissolved in solution B at a molar ratio of (1:1) by mechanically stirring at 1500 r / min for 30 min at 30°C to obtain solution C; Step 4: After reducing the temperature of solution C to -10°C, IPC was added at a molar ratio of (1:1) to MPD+PABZ for low-temperature polycondensation for 40 min to obtain colloid D; Step 5: Colloid D was heated and stirred, centrifuged and defoamed, and scraped to obtain thin film F1; specifically: Step 501: The temperature of colloid D was increased to 30°C and continuously mechanically stirred at 1500 r / min for 50 min to obtain colloid E1; Step 502: Colloid E1 was centrifuged and defoamed at 8000 r / min for 5 min to obtain colloid E2; Step 503: Colloid E2 was scraped onto a glass plate using a scraper at a scraping temperature of 25°C, a scraping speed of 15 mm / s, and a scraping thickness of 60 μm to obtain thin film F1; Step 6: Thin film F1 was placed in a coagulation bath H2O for 12 h to obtain thin film F2; Step 7: Thin film F2 was sequentially subjected to vacuum heat pressing pre-drying and vacuum drying to obtain imidazole-containing meta-aramid film G2; specifically: Step 701: Thin film F2 was pre-dried in a vacuum heat pressing dryer at 65°C under a vacuum degree of -0.09 MPa for 1 min to obtain thin film G1; Step 702: Thin film G1 was placed in a vacuum drying oven at a temperature of 60°C and a vacuum degree of -3 MPa for drying overnight for 12 h to obtain imidazole-containing meta-aramid film G2; Step 8: Thin film G2 was punched into a circular film with a diameter of 19 mm to obtain thin film H; Step 9: Thin film H was assembled in the battery according to the order of positive shell-positive electrode-separator-thin film H-negative electrode-gasket-elastic piece-negative shell to obtain the battery; The battery prepared in Example 3 was tested in a Li / / Cu half-cell at a current density of 1.0 mA·cm -1 The average coulombic efficiency of the Li / / Cu half-cell with the thin film H of Example 3 reached 88.41%, which was better than that of the traditional polyolefin separator (78.84%).
[0040] Example 4 Step 1, 30 min in advance to the three mouth flask into nitrogen, exhaust flask air, then LiCl powder and N, N-dimethylacetamide DMAc solvent with mass ratio (20:1) into the three mouth flask, 30 ℃ with a speed of 1500 r / min mechanical stirring 25 min, get solution A; Step 2: the mPEG powder is added to solution A at 40% of the final synthesis of meta-aramid resin, 30 ℃ with a speed of 1100 r / min mechanical stirring 25 min, get solution B; Step 3: the MPD powder and PABZ powder with a molar ratio of (3:4), 30 ℃ with a speed of 1500 r / min mechanical stirring 30 min to make it dissolved in solution B, get solution C; Step 4: the temperature of solution C is reduced to-10 ℃, then the IPC with a molar ratio of (1:1) of MPD+PABZ is added and low temperature polycondensation for 40 min, get colloid D; Step 5: colloid D is heated and stirred, centrifugal defoaming and scraping, get thin film F1; specific: Step 501: the temperature of colloid D is increased to 30 ℃ and continues to be stirred at a speed of 1500 r / min for 50 min, get colloid E1; Step 502: colloid E1 is centrifugal defoaming at a speed of 8000 r / min for 5 min, get colloid E2; Step 503: colloid E2 is scraped onto a glass plate using a scraper at a scraping temperature of 25 ℃, a scraping speed of 15 mm / s and a scraping thickness of 60 μm, get thin film F1; Step 6: thin film F1 is placed in the coagulation bath H2O for 12 h, get thin film F2; Step 7: thin film F2 is sequentially subjected to vacuum heat pressing pre-drying and vacuum drying, get imidazole containing meta-aramid film G2, specific: Step 701: thin film F2 is pre-dried in a vacuum heat pressing dryer at 65 ℃ under a vacuum degree of-0.09 MPa for 1 min, get thin film G1; Step 702: thin film G1 is placed in a vacuum drying oven at a temperature of 60 ℃ and a vacuum degree of-3 MPa for 12 h, get imidazole containing meta-aramid film G2; Step 8: thin film G2 is punched into a circular film with a diameter of 19 mm, get thin film H; Step 9: thin film H is assembled in the battery according to the order of positive shell-positive electrode-separator-thin film H-negative electrode-gasket-elastic piece-negative shell, get battery; The battery prepared in Example 4 was tested in a Li / / Cu half-cell at a current density of 1.0 mA·cm -1 100 cycles, and it was found that the average coulombic efficiency of the Li / / Cu half-cell with the thin film H in Example 4 reached 86.23%, which was better than that of the conventional polyolefin-based separator (78.84%).
[0041] Example 5 Step 1: Nitrogen was introduced into a three-neck flask 30 min in advance, and the air in the flask was exhausted. Then LiCl powder and N,N-dimethylacetamide (DMAc) solvent were added to the three-neck flask at a mass ratio (20:1), and mechanical stirring was performed at 30°C and a speed of 1500 r / min for 25 min to obtain solution A; Step 2: mPEG powder was added to solution A at 50% of the final synthesis amount of meta-aramid resin, and mechanical stirring was performed at 30°C and a speed of 1100 r / min for 25 min to obtain solution B; Step 3: MPD powder and PABZ powder were dissolved in solution B at a molar ratio of (1:2) by mechanical stirring at 30°C and a speed of 1500 r / min for 30 min to obtain solution C; Step 4: After the temperature of solution C was reduced to -10°C, IPC was added at a molar ratio of (1:1.02) with respect to MPD+PABZ, and low-temperature polycondensation was performed for 40 min to obtain colloid D; Step 5: Colloid D was heated and stirred, centrifuged and defoamed, and scraped to obtain thin film F1; specifically: Step 501: The temperature of colloid D was increased to 30°C, and mechanical stirring was continued at a speed of 1500 r / min for 50 min to obtain colloid E1; Step 502: Colloid E1 was centrifuged and defoamed at a speed of 8000 r / min for 5 min to obtain colloid E2; Step 503: Colloid E2 was scraped onto a glass plate using a scraper at a scraping temperature of 25°C, a scraping speed of 15 mm / s, and a scraping thickness of 75 μm to obtain thin film F1; Step 6: Thin film F1 was placed in a coagulation bath H2O for 12 h to obtain thin film F2; Step 7: Thin film F2 was subjected to vacuum hot-pressing pre-drying and vacuum drying in sequence to obtain imidazole-containing meta-aramid film G2; specifically: Step 701: Thin film F2 was pre-dried in a vacuum hot-pressing dryer at 65°C and a vacuum degree of -0.09 MPa for 1 min to obtain thin film G1; Step 702: The film G1 was placed into a vacuum drying oven with a temperature of 60℃ and a vacuum degree of -3 MPa overnight for 12 h to obtain an imidazole-containing meta-aramid film G2; Step 8: The film G2 was punched into a circular film with a diameter of 19 mm to obtain a film H; Step 9: The film H was assembled in the battery in the order of positive shell-positive electrode-separator-film H-negative electrode-gasket-elastic piece-negative shell to obtain a battery example 5; The battery prepared in example 5 was tested in a Li / / Cu half-cell at a current density of 1.0 mA·cm -1 The average coulombic efficiency of the Li / / Cu half-cell with the film H in example 5 reached 87.61%, which was better than that of the traditional polyolefin separator (78.84%). The above only describes the preferred embodiments of the present application, and does not use any limitation on the technical solutions of the present application. Those skilled in the art should understand that without departing from the spirit and principles of the present application, the technical solutions can also be modified and replaced in several simple ways, and these modifications and replacements also belong to the protection scope covered by the claims.
Claims
1. A method of making an imidazole-containing meta-aramid film, characterized by, Comprising the following steps: Step 1: stirring LiCl powder and DMAc solution uniformly under nitrogen atmosphere to obtain solution A; Step 2: dispersing mPEG powder in solution A, stirring uniformly to obtain solution B; Step 3: adding MPD powder and PABZ powder into solution B to obtain solution C; Step 4: cooling solution C to -20~0℃, adding IPC into the cooled solution C to obtain colloid D; Step 5: heating and stirring colloid D, centrifugal defoaming and scraping to obtain film F1; Step 6: placing film F1 in a coagulation bath to replace to obtain film F2; Step 7: sequentially performing vacuum heat pressing pre-drying and vacuum drying on film F2 to obtain imidazole-containing meta-aramid film G2.
2. The method of claim 1, wherein the imidazole-containing meta-aramid film is prepared by the steps of: In step 1, the nitrogen gas needs to be introduced in advance before synthesis, and needs to be continuously introduced for 15~30 min. And it also needs to be continuously introduced during the synthesis until the end of the synthesis; the stirring speed is always kept at 1000~1500 r / min; The mass ratio of DMAc solution to LiCl powder is 100:2~5, the stirring time is 20~60 min, and the stirring temperature is 20~30℃.
3. The method of claim 1, wherein the imidazole-containing meta-aramid film is prepared by the steps of: In step 2, the addition amount of mPEG powder is 5%~10% of the mass of solution A, the stirring time is 20~60 min, and the stirring temperature is 20~30℃.
4. The method of claim 1, wherein the imidazole-containing meta-aramid film is prepared by the steps of: In step 3, the molar ratio of MPD powder to PABZ powder is 3:(1~6), the stirring and dissolving time is 20~60 min, and the stirring temperature is 20~30℃.
5. The method of claim 1, wherein the imidazole-containing meta-aramid film is prepared by the steps of: In step 4, the molar ratio of the sum of MPD powder and PABZ powder to IPC powder is 1:(1~1.02), the low-temperature polycondensation time is 20~60 min, and the low-temperature polycondensation temperature is 0~-20℃.
6. The method of claim 1, wherein the imidazole-containing meta-aramid film is prepared by the steps of: In step 5, when heating and stirring, first heat colloid D to 25~65℃, then continuously stir for 20~60 min under the condition of maintaining the temperature; When centrifugal defoaming, the speed is 6000-8000 r / min, and the time is 3~10 min; When scraping, the temperature is 20~30℃, the speed is 5~20 mm / s, and the thickness is 50~75 μm.
7. The method for preparing and application of imidazole-containing meta- aramid film according to claim 1, characterized in that, In step 8, the coagulation bath is any one or several of H2O, C2H5OH, CH3OH, C3H8O3, DMAc / H2O, C2H5OH / DMAc or CH3OH / DMAc, and the replacement time is 12~24 h.
8. The method for preparing and application of imidazole-containing meta- aramid film according to claim 1, characterized in that, In step 10, when vacuum pre-drying, the temperature is 65~105℃, the time is 1~3 min, and the vacuum degree is -0.1~-0.09 MPa; When vacuum drying, the temperature is 60~80℃, the time is 12~24 h, and the vacuum degree is -2.5~-3 MPa.
9. An imidazole-containing meta-aramid film G2 prepared by the preparation method of any one of claims 1~8.
10. A battery, characterized by The battery is assembled in the order of positive electrode shell-positive electrode-separator-thin film H-negative electrode-gasket-spring piece-negative electrode shell, wherein the thin film is cut from the imidazole-containing meta-aramid film G2 obtained by the preparation method of any one of claims 1~8.